Obesity – A Matter of Motivation? - Hanssen, Ruth; Thanarajah, Sharmili E; Tittgemeyer, Marc; Brüning, Jens C. (Experimental and Clinical Endocrinology & Diabetes, 2022)
Excessive food intake and reduced physical activity have long been established as primary causes of obesity. However, the underlying mechanisms causing this unhealthy behavior characterized by heightened motivation for food but not for physical effort are unclear. Despite the common unjustified stigmatization that obesity is a result of laziness and lack of discipline, it is becoming increasingly clear that high-fat diet feeding and obesity cause alterations in brain circuits that are critical for the control of motivational behavior.In this mini-review, we provide a comprehensive overview of incentive motivation, its neural encoding in the dopaminergic mesolimbic system as well as its metabolic modulation with a focus on derangements of incentive motivation in obesity. We further discuss the emerging field of metabolic interventions to counteract motivational deficits and their potential clinical implications.
Keywords: Obesity; motivation; GLP-1; Dopaminergic midbrain